2011
DOI: 10.1088/0264-9381/28/9/094012
|View full text |Cite
|
Sign up to set email alerts
|

A scientific case study of an advanced LISA mission

Abstract: A brief status report of an ongoing scientific case study of the Advanced Laser Interferometer Antenna (ALIA) mission is presented. Key technology requirements and primary science objectives of the mission are covered in 0264-9381/11/094012+10$33.00

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 33 publications
0
51
0
2
Order By: Relevance
“…We indicate with a solid curve the noise curve f S h ( f ) for the ALIA detector with an armlength of 3 × 10 9 m, a telescope diameter of 0.58 m, and a 1-way position noise of 8/ √ Hz pm, i.e. the 3H configuration of Gong et al (2011). We also add the noise curve for a LISA-like detector (in grey, Larson et al 2000), with the Galactic binary white dwarf confusion background (Bender & Hils 1997).…”
Section: Discussionmentioning
confidence: 99%
“…We indicate with a solid curve the noise curve f S h ( f ) for the ALIA detector with an armlength of 3 × 10 9 m, a telescope diameter of 0.58 m, and a 1-way position noise of 8/ √ Hz pm, i.e. the 3H configuration of Gong et al (2011). We also add the noise curve for a LISA-like detector (in grey, Larson et al 2000), with the Galactic binary white dwarf confusion background (Bender & Hils 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The space-based detectors such as eLISA [18], LISA [19], Taiji [20] and Tianqin [21], will change much of their positions within the time scale of the gravitational wave signal. So the information of the gravitational wave source localization will be codded in the output signal of the space-based detector.…”
Section: Introductionmentioning
confidence: 99%
“…The main theme of the study was to look at possible GW sources around 0.01 Hz which was not entirely well understood at then. With ALIA [272,273] adopted as a representative mission concept around the 0.01 Hz band, further analysis revealed that there is a rich source of intermediate mass black hole binaries at high redshift and the detection would shed light on the black hole-galaxy coevolution during the structural formation pro-cess of the Universe [274].…”
Section: Gravitational Wave Detection In Spacementioning
confidence: 99%